Kiwisaldula waiho and K. hurunui, two new species of Saldidae (Hemiptera: Heteroptera) from the South Island of New Zealand, with redescriptions of K. butleri (White) and K. laelaps (White) - Larivière, Marie-Claude; Larochelle, André (Zootaxa, 2017)
Kiwisaldula waiho new species and K. hurunui new species, are described from the South Island of New Zealand. Kiwisaldula butleri (White, 1878) and K. laelaps (White, 1878), two taxonomically little-known taxa, are redescribed. Morphological descriptions are provided together with illustrations emphasising the most important diagnostic features of external morphology and male genitalia. Information is given on synonymy, type specimens, material examined, geographic distribution and biology.